Penguatan Pemahaman Masyarakat Terhadap Kelestarian Mangrove Bagi Mayarakat Asli Papua untuk Mewujudkan Kawasan Pesisir Berkelanjutan serta Mendukung Ekonomi Biru - Sianturi, Reny; Nurliah, Nurliah; Xaferius, Fransiskus (Universitas Muhammadiyah Mataram, 2026)
Abstract: Mangroves are ecosystems that live in the transitional area between the ocean and land. Mangrove ecosystems play a key role in the sustainability of coastal areas. The existence of mangrove ecosystems is key to sustainability because it provides various important benefits both physically, ecologically, socially, and economically. These benefits are greatly felt by coastal communities whose areas have mangrove potential, namely Buti village, Merauke Regency, South Papua Province. Buti village is one of the unique villages and is located in the center of Merauke Regency city because the majority of the residents are the indigenous Merauke tribe (Marind). The existence of the mangrove ecosystem in Buti village affects the economic conditions of the community, because most of them make a living as fishermen. Along with developments and changes in ecological, social and economic aspects, Buti village will face challenges in maintaining and using natural resources sustainably, especially in the mangrove ecosystem. Although Buti village has quite potential natural resources, the lack of information and data regarding mangrove potential will hinder future development. Based on the emergence of several problems, the Community Service team implemented several programs as solutions to existing problems. The program included mapping mangrove potential using remote sensing technology, specifically the Mangrove Vegetation Index (MVI) from Landsat 8 satellite imagery, and providing outreach on mangrove utilization and conservation efforts. The results of the community service activities indicate that Buti village has significant mangrove potential mapped and a fairly good understanding of mangrove sustainability.Abstrak: : Mangrove merupakan ekosistem yang hidup di wilayah peralihan antara lautan dan daratan. Ekosistem mangrove memiliki peran sebagai kunci dalam keberlanjutan wilayah pesisir. Peran tersebut sangat dirasakan oleh masyarakat pesisir yang wilayahnya terdapat potensi mangrove, yaitu kampung Buti, Kabupaten Merauke, Provinsi Papua Selatan. perekonomian masyarakat, karena sebagian besar bermata pencaharian sebagai nelayan. Seiring dengan perkembangan dan perubahan dari segi ekologi, sosial dan ekonomi, kampung Buti akan menghadapi tantangan untuk menjaga dan memanfaatkan sumberdaya alam secara berkelanjutan khususnya di ekosistem mangrove.. Berdasarkan dengan kemunculan beberapa permasalahan tersebut, tim Pengabdian kepada Masyarakat. Tujuan dari kegiatan ini yaitu untuk melakukan pemetaan potensi mangrove dan penyuluhan pemanfaatan mangrove sebagai upaya pelestarian berkelanjutan. Metode yang digunakan dengan metode Mangrove Vegetation Index (MVI) dari citra satelit Landsat 8 dan penyuluhan. Hasil kegiatan pengabdian kepada masyarakat bahwa kampung Buti memiliki pemetaan potensi mangrove yang potensial dan pemahaman terhadap kelestarian mangrove yang cukup baik.